I am assuming $b$ is the OLS estimate of $\beta$ and $e$ is the corresponding estimate of $\epsilon$. Also I believe you have a typo above in your expression, as there should be $X'$ in front of $\epsilon \epsilon'$ and behind $(X'X)^{-1}$.
Start with the definition of $b$:
$$b=(X'X)^{-1}X'Y.$$
Replacing $Y$ with $X\beta+\epsilon$ in our expression above, we get
$$b=(X'X)^{-1}X'(X\beta+\epsilon)=\beta+(X'X)^{-1}X'\epsilon.$$
It follows that
$$b-\beta = (X'X)^{-1}X'\epsilon$$
Now turn to the defintion of $e$:
$$e=Y-\hat{Y}=Y-Xb=Y-X(X'X)^{-1}X'Y.$$
Notice $X(X'X)^{-1}X'$ is the projection matrix for $X$, which we will denote with $P_{[X]}$.
Replacing this in our expression for $e,$ we get
$$e=(I-P_{[X]})Y=M_{[X]}Y.$$
Replacing $Y$ in the expression above with $X\beta+\epsilon$, we get
$$e=M_{[X]}(X\beta+\epsilon)=M_{[X]}\epsilon,$$
since $M_{[X]}X$ is a matrix of zeros.
Post-multiplying $b-\beta$ with $e'$, we get
$$(b-\beta)e'=(X'X)^{-1}X'\epsilon \epsilon' M_{[X]},$$
since $e'=\epsilon'M_{[X]}.$